Plasma fatty acid profile comparisons between the lesser mouse deer (Tragulus javanicus) and the common muntjac (Muntiacus muntjak) - Goh, Yong Meng; Abas, Suwaibatul Aslamiah; Goriman Khan, Mohd Azam Khan; Che Amat, Azlan; Ahmad, Hafandi (Veterinary Association Malaysia, 2006)
The Lesser Mouse Deer and the Common Muntjac are native to the South-east Asian region. The main aim of this study was to compare the extent of plasma fatty acid unsaturation between these two species. Dietary unsaturated fatty acids are expected to undergo extensive biohydrogenation and saturation in the gut of the Common Muntjac, as is expected for a 'true' ruminant. Being a 'partial' ruminant, the Lesser Mouse Deer is expected to allow some dietary unsaturated fatty acids to escape rumen biohydrogenation, thus allowing accumulation of more unsaturated fatty acids in the plasma. Six Lesser Mouse Deer and six Common Muntjac, kept for recreational purposes, were used in this study. Plasma fatty acids were extracted from blood and feed samples, methylated using 14 % boron triflouride and separated using gas liquid chromatography. It was found that both species had higher unsaturated fatty acid content in their plasma compared to saturated fatty acids. This is different from domesticated ruminants where saturated fatty acids usually are about 60 % of total plasma fatty acids. The plasma unsaturated fatty acid content of the Lesser Mouse Deer is marginally higher (52.9 %) than the Common Muntjac (51.8 %). However, the Lesser Mouse Deer had higher plasma n-6 polyunsaturated fatty acids (PUFA) at 16 %, and a more balanced n-3 PUFA content. This resulted in better and lower n-6 PUFA: n-3 PUFA ratios in the Lesser Mouse Deer (4.2). These findings could be attributed to the reduced biohydrogenation and destruction of dietary unsaturated fatty acids in the gut of Lesser Mouse Deer, thus enabling more of these fatty acids to be absorbed by the body. In conclusion, true and partial wild ruminants found to have different plasma fatty acid profile as a result of their differences in gut function and morphology